Type III Monteggia Injury With Ipsilateral Distal Forearm Fracture in a Child: A Case Report - Chao Gao; Jing Hua Sun; Hua Jiang Zheng; Yong Yao Wu; Jin Cao (Frontiers Media S.A., 2022)
Monteggia fracture refers to breakage of the upper third of the ulna combined with dislocation of the radial head. It often occurs in children and adolescents and represents a combined injury. Fracture of the distal forearm is among the most common trauma suffered by children. However, distal forearm fractures have rarely been reported as having an association with Monteggia fractures. We report on a 9-year-old boy diagnosed with a type III Monteggia fracture combined with a distal forearm fracture. He underwent surgery and received rehabilitation training 1 month later. He was followed-up for 1 year. The affected limb functioned well with no sign of radial head dislocation.